The Adjudication of Marriage Disputes through Mediation at the Manado Religious Court - Faradila Hasan; Nasruddin Yusuf; Moh. Muzwir R. Luntajo (INNOVATIO: Journal for Religious Innovation Studies, 2020)
Abstract: The phenomenon of marital disputes that often end in divorce has been a serious concern of the government, resulting in a regulation on mediation, namely the Regulation of the Supreme Court of Republic of Indonesia (PERMA) Number 1 of 2016. This regulation was made with the hope of reducing the divorce rate caused by marriage disputes. This article discusses the form of marriage dispute resolution at Manado Religious Court with a focus on one type of dispute resolution, namely mediation. This study uses an empirical juridical approach. The research was conducted at the Manado City Religious Court in 2017 and 2020. The result is that the mediation process has been carried out in accordance with the provisions of PERMA No.1 of 2016. However, there have been many obstacles. Thus, the efforts to reduce the divorce rate due to marriage disputes have not undergone significant changes. Keywords: mediation; marriage dispute; Manado religious court. Abstrak: Fenomena sengketa perkawinan yang sering berakhir pada perceraian menjadi perhatian serius dari pemerintah sehingga melahirkan aturan tentang mediasi yaitu Peraturan Mahkamah Agung RI (PERMA) No. 1 Tahun 2016. Aturan ini dibuat dengan harapan menekan angka perceraian yang diakibatkan oleh sengketa perkawinan. Artikel ini membahas mengenai bentuk penyelesaian sengketa perkawinan di Pengadilan Agama Manado dengan fokus pada salah satu jenis penyelesaian sengketa yaitu mediasi. Penelitian ini menggunakan pendekatan yuridis empiris. Penelitian ini dilakukan di Pengadilan Agama Kota Manado pada tahun 2017 dan tahun 2020. Hasilnya adalah proses mediasi sudah dilakukan sesuai dengan ketentuan PERMA No.1 Tahun 2016. Namun mengalami benyak kendala sehingga upaya untuk menekan angka perceraian akibat sengketa perkawinan belum mengalami perubahan yang signifikan. Kata-kata kunci: mediasi; sengketa perkawinan; pengadilan agama Manado.